Sustainable Design: Circular Economy in Fashion and Textiles - Moorhouse, Debbie; Moorhouse, Danielle (The Design journal, 2017)
Fashion is widely considered the second most destructive industry after oil, to the environment. An EU initiative called the European Clothing Action Plan has been launched to significantly improve by 2019 the sustainability of textiles across their life cycle from design to end of use. Textile waste ending up in landfills has become a huge concern globally. If every brand along the clothing supply chain begin to implement eco-friendly practices, the textile and fashion industries will become significantly more sustainable. Up to 95% of textiles land filled, each year could be recycled. (pure waste.org) With an increasing concern amongst consumers about the social and environmental impact of their purchases, businesses are beginning to understand the benefits and untapped economic potential of efficient use of waste.